2022
DOI: 10.1186/s12977-022-00589-1
|View full text |Cite|
|
Sign up to set email alerts
|

YTHDC1 regulates distinct post-integration steps of HIV-1 replication and is important for viral infectivity

Abstract: Background The recent discovery of the role of m6A methylation in the regulation of HIV-1 replication unveiled a novel layer of regulation for HIV gene expression. This epitranscriptomic modification of HIV-1 RNAs is under the dynamic control of specific writers and erasers. In addition, cytoplasmic readers of the m6A mark are recruited to the modified viral RNAs and regulate HIV-1 replication. Yet, little is known about the effects of m6A writers and readers on the biogenesis of HIV-1 RNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The timing of m 6 A deposition (occurring before or after splicing) is key to understanding the connection, but it appears to be complex 52 55 , 70 73 . Notably, gene-specific or virus-specific investigations have established clearer links between m 6 As and alternative splicing, involving m 6 A writers 74 77 , the nuclear reader YTHDC1 9 , 10 , 78 and erasers 7 , 79 , 80 , as well as interactions with splicing regulatory elements 16 19 , 69 , 81 . However, the impact of YTHDC1 knockdown on HIV-1 alternative splicing appeared controversial in two recent studies 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of m 6 A deposition (occurring before or after splicing) is key to understanding the connection, but it appears to be complex 52 55 , 70 73 . Notably, gene-specific or virus-specific investigations have established clearer links between m 6 As and alternative splicing, involving m 6 A writers 74 77 , the nuclear reader YTHDC1 9 , 10 , 78 and erasers 7 , 79 , 80 , as well as interactions with splicing regulatory elements 16 19 , 69 , 81 . However, the impact of YTHDC1 knockdown on HIV-1 alternative splicing appeared controversial in two recent studies 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, gene-specific or virus-specific investigations have established clearer links between m 6 As and alternative splicing, involving m 6 A writers 74 77 , the nuclear reader YTHDC1 9 , 10 , 78 and erasers 7 , 79 , 80 , as well as interactions with splicing regulatory elements 16 19 , 69 , 81 . However, the impact of YTHDC1 knockdown on HIV-1 alternative splicing appeared controversial in two recent studies 9 , 10 . G-quadruplexes (G4s), co-localized with the three major m 6 A sites, might also influence alternative splicing 82 , 83 .…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear m 6 A reader YTHDC1 is known to be involved in RNA stability and splicing and the nuclear export of m 6 A-modified viral and cellular RNA [ 3 , 64 , 65 ]. Two independent studies assessed HIV-1 RNA splicing and nuclear export under conditions of overexpression or depletion of YTHDC1 during single-round infections [ 26 , 66 ]. Both studies found that YTHDC1 is required for not only maintaining overall viral RNA levels but also for the appropriate selection of splice sites.…”
Section: M 6 a Regulates Hiv-1 Rna Splicing And Nu...mentioning
confidence: 99%
“…This suggests that the observed changes in HIV-1 RNA upon YTHDC1 silencing or overexpression are due to the presence of m 6 A ( Figure 2 ). Overexpressed and endogenous YTHDC1 bind to spliced and unspliced HIV-1 RNA in infected cells in a METTL3-dependent manner [ 66 ] ( Figure 2 ). YTHDC1-binding sites were identified adjacent to HIV-1 splice acceptor (SA) sites 3 and 7 [ 60 ].…”
Section: M 6 a Regulates Hiv-1 Rna Splicing And Nu...mentioning
confidence: 99%
See 1 more Smart Citation